Kenya : Request for an Extension of the Arrangement Under the Extended Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper requests an extension of the 12-month Stand By Arrangement and the Standby Credit Facility Arrangement to obtain enough time to finalize fiscal measures for 2015/16 and implement structural measures under the program. Although at a slower-than-projected pace, the economy continued to expand robustly. Driven by public infrastructure spending, buoyant credit growth, and strong customer demand, real GDP is estimated to have grown by 5.6 percent in 2015. As per the staff's assessment based on recent data, performance under the current program remains broadly satisfactory. Staff fully supports the authorities' request for extensions of the arrangements through March 15, 2016.